SIRT4 prevents excitotoxicity via modulating glutamate metabolism in glioma cells. (July 2020) - Yalçın, G Dönmez; Colak, M
Excitotoxicity is the presence of excessive glutamate, which is normally taken up by glutamate transporters on astrocytes. Glutamate transporter 1 (GLT-1) is the major transporter on glia cells clearing more than 90% of the glutamate. Sirtuin 4 (SIRT4) is a mitochondrial sirtuin which is expressed in the brain. Previously, it was shown that loss of SIRT4 leads to a more severe reaction to kainic acid, an excitotoxic agent, and also decreased GLT-1 expression in the brain. In this study, we aimed to investigate whether overexpression of SIRT4 is protective against excitotoxicity in glia cells. We overexpressed SIRT4 in A172 glioma cell line and treated with kainic acid in order to induce excitotoxicity. We observed that SIRT4 overexpression increased the cell viability after kainic acid treatment. In addition, reduced glutamate was detected in glutamate assay with overexpression of SIRT4 after kainic acid treatment since SIRT4 decreased cell death by preventing excitotoxicity. Our results show that overexpression of SIRT4 increased the protein levels of GLT-1 and glutamate dehydrogenase (GDH) after kainic acid (KA) treatment so that excess glutamate can be absorbed. However, overexpression of SIRT4 decreased glutamine synthetase (GS) levels. These results demonstrate that, by inhibiting GS, SIRT4 prevents glutamine formation, which will be converted to glutamate in neurons. SIRT4 prevents excitotoxicity via upregulating glutamate metabolism. Finally, our results may show that SIRT4 might prevent excitotoxicity and related cell death via reducing GS expression and upregulating GLT-1 and GDH levels. Therefore, it is important to develop therapeutics against excitotoxicity through SIRT4-related pathways in the cell.